HUBUNGAN TEKANAN DARAH DAN NADI TERHADAP KUALITAS HIDUP PASIEN HEMODIALISA DI RSUD PANEMBAHAN SENOPATI BANTUL - Muhammad Sholimin; Cornelia D.Y Nekada; Christin Wiyani (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Patients with chronic kidney disease undergoing hemodialysis experience many physical, psychological, and social changes associated with the disease process and the patient's ability to adapt to changes. Chronic kidney disease with hemodialysis is associated with physical symptoms and complications. Physical symptoms can be seen from the status of blood pressure and pulse. A total of 4 people have high blood pressure or hypertension and 1 person has normal blood pressure. In addition, it also causes neurological disorders and gastrointestinal disorders which have an impact on the quality of life of sufferers. Each of these physical changes has the potential to reduce quality of life. Objective: To determine the relationship between blood pressure and pulse on the quality of life of patients with chronic kidney failure undergoing hemodialysis. Methods: This type of research is quantitative with a descriptive correlative method using a cross sectional approach. The study population was 198 respondents. Respondents in this study were 67 respondents and the sample was taken using purposive sampling. The statistical test in this study used the Somers'd correlation test, with an error rate of α 5%. Results: The majority of blood pressure frequencies in the hypertension category were 66 respondents (98.5%), while the majority pulse frequency in the normal category were 57 respondents (85.1%). Statistical analysis of the relationship between blood pressure and quality of life obtained p value 0.329. Meanwhile, the statistical analysis of the relationship between pulse and quality of life was obtained p value 0.320. Conclusion: There is no correlation between blood pressure and pulse and quality of life in hemodialysis patients at Panembahan Senopati Hospital, Bantul.